Evaluative utterances in Zygmunt Ziembiński’s theory of law - Zirk-Sadowski, Marek (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
The study focuses on the methodological views of Zygmunt Ziembiński, against the background of the axiological issues addressed in his scientific investigations. In this respect, the author distinguishes three development periods in Ziembiński’s work; the first was dominated by a psychologist and empiricist approach to axiology, whereas the onset of the second was marked by a semiotic-pragmatic turn. In both periods, the essence and properties of evaluative utterances became the chief object of inquiry. In the last phase of his work, however, Ziembiński devoted himself to the study of the values manifesting in law, writing chiefly about justice and the constitution.